Procena nivoa oksidativnog stresa, nivoa 3-nitrotirozina i HMGB-1 kod pacijenata sa starosnom makularnom degeneracijom mokrog tipa: Oxidative stress, 3-NT, and HMGB-1 levels in patients with wAMD - Zor, Kürşad Ramazan; Sarı, İsmail and Gamze and Güntürk, İnayet and Küçük, Erkut and Erşan, Serpil and Seydel, Gönül Şeyda (Journal of Medical Biochemistry, 2021)
Abstract Background: This study aims to compare serum HMGB-1, 3-nitrotyrosine (3-NT), TAS, TOS, and OSI levels in Wet-type Age-Related Macular Degeneration (wAMD) patients and healthy controls to determine the correlation of these parameters with each other. Methods: Thirty patients with Wet-type Age-Related Macular Degeneration (wAMD) and 27 healthy adults, as controls were enrolled in the study. We determined the TAS and TOS levels in serum samples of both groups using commercial kits on a microplate reader. Serum HMGB-1 and 3-NT levels were measured with the enzyme-linked immunosorbent assay method. Results: HMGB-1 levels were significantly higher in the patient group (137.51 pg / mL, p=0.001), while there was no difference between the two groups in serum 3-NT levels (p=0.428). A statistically significant difference found in the levels of TOS and OSI (p=0.001 and p=0.045, respectively) between the patients and controls, however, no significant difference was observed between the groups in terms of TAS levels (p=0.228). Conclusions: Oxidative stress and HMGB-1 levels were increased in wAMD patients and enhanced oxidative stress may be associated with increased tissue necrosis and inflammation. Thus administration of antioxidant treatment in addition to routine therapy should be considered in wAMD.